Project BBChina: a new Master Program in three Chinese Universities on Bio-Based Circular Economy; from Fields to Bioenergy, Biofuel and Bioproducts. (February 2019) - Nibbi, Leonardo; Chiaramonti, David; Palchetti, Enrico
Abstract: Six Higher Education Institutions among China and Europe have agreed to work together in order to establish and implement a 120 ECTS equivalent Master Program on Bio-Based Circular economy in three Chinese Universities. The aim is to start the first edition of the Master in September 2019 in the following Universities: Tongji University and East China University of Science and Technology, both from Shanghai, and the Sichuan University of Chengdu. The Master will be implemented within the BBChina Project, supported by the Education, Audiovisual and Culture Executive Agency of the European Commission under the ERASMUS+ programme. The project BBChina, started in autumn 2017, aims to help People's Republic of China fully exploiting its wide bioenergy potential, thus strongly decreasing the present use of fossil fuels that dramatically increases the local pollution and that is strongly affecting the pollution at world level as well as global warming. To reach the aim, the newly established Master program will deeply analyse the complex chain that starts from the biomass production and collection until the output of biorefineries, to the bioenergy production, to the biofuel utilisation as well as to the always more important integration with other Renewable Energy Sources (RES). Furthermore, the program will include education and training activities such as technical laboratory, international mobility of teacher and students, seminaries, and actions to trigger and encourage young entrepreneurship and innovation in the global green market scenario.